A Family of Nonconforming Rectangular Elements for Strain Gradient Elasticity (Advances in Applied Mathematics and Mechanics, 2021)
We propose a family of nonconforming rectangular elements for the linear strain gradient elastic model. Optimal error estimates uniformly with respect to the small material parameter have been proved. Numerical results confirm the theoretical prediction.